Theological Reflections on the Temptation of Christ based on a comparative study between the Accounts of Matthew and Luke - Samuel Asare-Antwako; Isaac Boaheng (E-Journal of Humanities, Arts and Social Sciences)
This paper explored the theological implications of the temptation of Christ as depicted in the Gospels of Matthew and Luke. Through a comparative study of these accounts, the paper examined the nuanced differences and similarities. The paper conducted a textual analysis of key expressions in the text to arrive at a theological conclusion. The analysis examined the significance of Christ’s temptation in relation to his identity, mission, and the broader narrative of salvation history. The study revealed variations in the narrative placement and structure of the temptation accounts in both Mathew and Luke due to their different motifs. The study also revealed the crucial role of the Holy Spirit in the temptation accounts in both Matthew and Luke, with different nuances. Again, the study also revealed that the nuanced differences in the duration, the nature of the fast and the temptation contents in Matthew and Luke highlight various theological emphases and narrative strategies. By juxtaposing the perspectives presented in Matthew and Luke, this paper seeks to deepen understanding of the theological insights conveyed through the temptation narrative, highlighting its relevance for contemporary Christian reflection and spiritual formation. The paper concludes by asserting that the temptation accounts in Matthew and Luke emphasized the sovereignty and providence of God and the authority of scripture. It also stressed the interplay between pneumatology and human experience during temptation periods and placed Jesus ahead as the model for spiritual dependence on God.